2013
DOI: 10.3390/molecules18066883
|View full text |Cite
|
Sign up to set email alerts
|

Arylsulfonylamino-Benzanilides as Inhibitors of the Apical Sodium-Dependent Bile Salt Transporter (SLC10A2)

Abstract: Abstract:The apical sodium-dependent bile salt transporter (ASBT) plays a pivotal role in maintaining bile acid homeostasis. Inhibition of ASBT would reduce bile acid pool size and lower cholesterol levels. In this report, a series of novel arylsulfonylaminobenzanilides were designed and synthesized as potential inhibitors of ASBT. Most of them demonstrated great potency against ASBT's bile acid transport activity. In particular, compound 5g 2 inhibited ASBT activity with an IC 50 value of 0.11 μM. These compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…As demonstrated in previous studies [11], IMB17-15 is a novel and potent ASBT inhibitor. Consistent with the results of other ASBT inhibitor-related studies [9], our results showed that IMB17-15 increased the blood and hepatic BA levels and impaired the ileal BA absorption.…”
Section: Imb17-15 Treatment Altered Ba Composition and Increased Fecasupporting
confidence: 62%
See 1 more Smart Citation
“…As demonstrated in previous studies [11], IMB17-15 is a novel and potent ASBT inhibitor. Consistent with the results of other ASBT inhibitor-related studies [9], our results showed that IMB17-15 increased the blood and hepatic BA levels and impaired the ileal BA absorption.…”
Section: Imb17-15 Treatment Altered Ba Composition and Increased Fecasupporting
confidence: 62%
“…Recently, we synthesized a series of novel potent ASBT inhibitors using cell-based in vitro assays [11], including N-(3,4dichlorophenyl)−2-(3-trifluoromethoxy) benzamide, which is also referred to as IMB17-15 ( Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…HEK293T cells were seeded in 12-well plates and transiently transfected with 0.5 μg/well pcDNA3.1/ASBT or the negative control plasmid pcDNA3.1 using lipofactamine 2000 (Invitrogen, Carlsbad, CA, USA) according to the manufacturer׳s instructions. Twenty-four hours after transfection, HEK293T cells were assayed for taurocholic acid uptake as previously described with minor modifications 16 . Briefly, cells were washed twice with warm wash and uptake buffer (116 mmol/L NaCl, 5.3 mmol/L KCl, 1.1 mmol/L KH 2 PO 4 , 0.8 mmol/L MgSO 4 , 1.8 mmol/L CaCl 2 , 11 mmol/L d -dextrose/ d -glucose, and 10 mmol/L HEPES, pH 7.4), and then incubated with the same buffer containing the indicated concentrations of test compounds (dissolved in dimethyl sulfoxide) and 1 μCi/mL of [ 3 H]-taurocholic acid (TCA, 0.2 μmol/L) (PerkinElmer Life Sciences) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has been dedicated to the investigation and development of ASBT inhibitors and has obtained a series of compounds with good activity 16 . NC-1, a compound obtained by extensive screening in our lab, was found to have potent ASBT inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these series is built upon on anthranilic amide core. The anthranilic amide scaffold has found use in small molecules targeted at a range of therapeutic applications: management of chronic pain 14 16 and inflammation, 17 reduction of cholesterol levels, 18 , 19 inhibition of hepatitis C, 20 and anticancer therapeutics. 21 , 22 Peukert et al identified a series of anthranilic amide-based Kv1.5 channel blockers with moderate oral bioavailability and no significant hERG inhibition.…”
Section: Introductionmentioning
confidence: 99%